Revealing Public Service Quality: Assessing Satisfaction Levels and Performance in a Local Administrative Unit - Lestari, Arum Putri Damayanti; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2023)
This study delves into the pivotal role of service quality in organizational development, focusing on public service satisfaction at the Suko Village Office, Sidoarjo Sub-district, Sidoarjo Regency. Employing a descriptive quantitative approach through survey methodology, 390 respondents were randomly sampled. Data collection involved primary and secondary sources, while analysis utilized the Community Satisfaction Index (CSI) based on 9 service elements following the Indonesian Minister of Administrative and Bureaucratic Reform Regulation No. 14/2017. Results reveal an average score of 0.111 across the 9 service elements, with the perception interval indicating service quality and performance falling within the